'Bhavishya Shakti: Empowering the Future': establishing and evaluating a pilot community mobile teaching kitchen as an innovative model, training marginalised women to become nutrition champions and culinary health educators in Kolkata, India. Issue 2 (28th July 2021) - Buckner, Luke; Carter, Harrison; Crocombe, Dominic; Kargbo, Sento; Korre, Maria; Bhar, Somnath; Bhat, Shivani; Chakraborty, Debashis; Douglas, Pauline; Gupta, Mitali; Maitra-Nag, Sudeshna; Muhkerjee, Sagarika; et al.
Abstract : Background: Malnutrition is a global emergency, creating an overlapping burden on individual, public and economic health. The double burden of malnutrition affects approximately 2.3 billion adults worldwide. Following 3 years of capacity building work in Kolkata, with assistance of local volunteers and organisations, we established an empowering nutrition education model in the form of a 'mobile teaching kitchen (MTK)' with the aim of creating culinary health educators from lay slum-dwelling women. Aims: To evaluate the piloting of a novel MTK nutrition education platform and its effects on the participants, alongside data collection feasibility. Methods: Over 6 months, marginalised (RG Kar and Chetla slums) women underwent nutrition training using the MTK supported by dietitians, doctors and volunteers. Preintervention and postintervention assessments of knowledge, attitudes and practices (KAP), as well as anthropometric and clinical nutritional status of both the women and their children were recorded. The education was delivered by a 'See One, Do One, Teach One' approach with a final assessment of teaching delivery performed in the final session. Results: Twelve women were trained in total, six from each slum. Statistically significant improvements were noted in sections of KAP, with improvements in nutrition knowledge (+4.8) and practices (+0.8). In addition, statistically significant positive changes were seen in 'understanding of healthy nutrition for their children' (p=0.02), 'sources of protein rich food' (p=0.02) and 'not skipping meals if a child is ill' (p≤0.001). Conclusion: The MTK as a public health intervention managed to educate, empower and upskill two groups of lay marginalised women into MTK Champions from the urban slums of Kolkata, India. Improvements in their nutrition KAP demonstrate just some of the effects of this programme. By the provision of healthy meals and nutritional messages, the MTK Champions are key drivers nudging improvements in nutrition and health related awareness with a ripple effect across the communities that they serve. There is potential to upscale and adapt this programme to other settings, or developing into a microenterprise model, that can help future MTK Champions earn a stable income.